A new deep-sea sponge Fibulia occiensis sp. nov. (Poecilosclerida: Dendoricellidae) from the 25° South Oceanic Core Complex in the Central Indian Ocean Ridge - Rengaiyan, Periasamy; Palayil, John Kurian; Ingole, Baban (Zootaxa, 2022)
We describe a new deep-sea sponge species, Fibulia occiensis sp. nov., from the Central Indian Ocean Ridge (CIOR) at Rodrigues Triple Junction (RTJ), of the family Dendoricellidae Hentschel, 1923. Two sponge specimens were collected between 1982–2079 m depth using a benthic sledge in the 25° South Oceanic Core Complex (OCC) region. The megabenthic fauna was collected to establish a baseline of environmental and benthic ecological data. This data will be handy in assessing the impact of sulfide mining in the near future. Fibulia occiensis sp. nov. is fragile and stalked, has a single type of oxea, and no sigma. The new species is different from the congeneric Fibulia species by its larger oxeas and the strongly curved isochelae.